Sistem Pengendalian Internal Dalam Pengelolaan Anggaran Pada Kantor Wilayah Kementerian Agama Provinsi Gorontalo - Wawan Loleh (CV. Dalle’ Deceng Abeeayla, 2024)
This research aims to determine the internal control system in budget management and what factors hinder the internal control system in budget management at the Regional Office of the Ministry of Religion, Gorontalo Province. This research uses a qualitative approach with an approach to the research object by extracting information according to the perceptions of researchers and informants and can develop according to the interactions that occur in the interview process. The research results show that several government internal control activities include performance reviews, human resource development, information system control, physical control of assets, determining performance measures, separation of functions, authorization of transactions and events, accurate and timely recording, limiting access to resources. , accountability for resources, and documentation of the internal control system. Apart from that, the inhibiting factors are power factors, institutional characteristics, compliance, budget, human resources, awareness, capabilities, facilities and infrastructure. The conclusion obtained in this research is that there is still a lack of commitment from the Head of the Regional Office of the Ministry of Religion of Gorontalo Province to implement SPI in accordance with applicable regulations and from the results of the research conducted, researchers hope that the processinternalisationSPI needs to be supported by implementationhard control, For this reason, it is necessary to have supporting devices in the form ofStandard Operating Procedure (SOP) and Task Force (Satgas) for SPI implementation.